Conjunctival melanoma in children: a systematic review - Maria Partyka; Julia Plewniok; Maksymilian Janeczek; Karolina Kinga Kantor; Wiktoria Maria Szymańska; Julia Wójcik; Kacper Wojciech Pamuła; Marcin Cholewa; Maciej Kuca; Karolina Jaglarz (Journal of Education, Health and Sport)
Introduction and Objective: Conjunctival melanoma (CM) is rare, particularly in children. It’s characterized by high aggressiveness and a tendency to metastasize. Due to the limited number of published case reports and studies in the pediatric population, it’s difficult to standardize diagnostic and therapeutic procedures. The aim of this paper is to collect and systematize the available information on cases of conjunctival melanoma in children.